Meniscal Ramp Lesion Repair Using the FasT-Fix Technique: Evaluating Healing and Patient Outcomes with Second-Look Arthroscopy - Chen, Zhong; Li, Wei-Ping; Yang, Rui; Song, Bin; Jiang, Chuan; Hou, Jing-Yi; Luo, Huan; Zhou, Yun-Feng (The Journal of Knee Surgery, 2018)
Although the suture-hook technique remains popular for meniscal ramp lesions, which frequently occur after anterior cruciate ligament (ACL) injury, it is unclear whether the all-inside FasT-Fix technique (Smith & Nephew, Andover, MA) is appropriate for the repair of ramp lesions. This study evaluated results of arthroscopic FasT-Fix meniscal ramp lesion repair using second-look arthroscopy. From August 2010 to December 2014, 46 knees diagnosed with combined ACL injury and ramp lesion underwent ACL reconstruction with meniscal repair using the FasT-Fix technique. We classified ramp lesions into three types according to tear pattern: meniscotibial ligament tear, meniscocapsular tear, and combined meniscotibial/meniscocapsular tear. Second-look arthroscopy was performed postoperatively. The healing capacity of the ramp lesion was evaluated retrospectively. At the final follow-up (mean = 32 months), the Lysholm knee score and the International Knee Documentation Committee (IKDC) objective score were compared with preoperative scores. All patients (n = 46) underwent a second-look arthroscopy, with 45 (97.8%) exhibiting complete or partial healing after the FasT-Fix technique was used in conjunction with ACL reconstruction. The Lysholm knee score and IKDC objective score were significantly better than preoperative scores at final follow-up. The FasT-Fix technique for meniscal ramp lesion repair—when performed with concomitant ACL reconstruction—exhibits excellent healing results.
Keywords: anterior cruciate ligament; medial meniscus; posterior horn; repair; healing; ramp lesion